STRATEGI GURU DALAM MENGGUNAKAN METODE FONIK UNTUK MENGATASI KESULITAN MEMBACA PERMULAAN DI KELAS II SD NEGERI 2 CIKAMARANG - Risnawati Ardanis; Asep Sahrul Gunawan (STKIP Subang, 2026)
Early reading difficulties among elementary school students are a common issue that can affect their future academic success. This study aims to analyze teachers’ strategies in using the phonics method to overcome early reading difficulties in second-grade elementary school students. The research employed a qualitative approach using a Systematic Literature Review (SLR) by analyzing 15 SINTA-indexed journal articles and 3 relevant reference books. Data collection was conducted through reviewing, identifying, and synthesizing literature related to the research focus. The results indicate that teachers’ strategies in implementing the phonics method are carried out in stages, including introducing letter sounds, blending sounds into syllables, and reading simple words and sentences. In addition, the use of various instructional media such as letter cards, pictures, and educational games has been proven to increase students’ interest and engagement in the learning process. The phonics method is effective in helping students understand the relationship between letters and sounds, thereby improving early reading skills. The success of this strategy is also influenced by teachers’ competence, the use of engaging learning media, and support from the family environment.